Aberrant expression of FBXO22 is associated with propofol-induced synaptic plasticity and cognitive dysfunction in adult mice - Yang, Xiaoxuan; Chen, Chen; Qu, Dongmei; Liu, Yanping; Wang, Ning; Wang, Haibi; Fan, Youjia; Zhou, Yushan; Yu, Buwei; Xue, Qingsheng; Wu, Yuqing; Lu, Han (Frontiers in Aging Neuroscience, 2022)
Recent observation demonstrated that prolonged anesthesia modifies brain synaptic architecture in all ages, including adult. Propofol is the most commonly utilized anesthetics at clinic. Whether repeated administration of propofol modulates cognitive impairment in adults and changes synaptic plasticity remains, however, to be explored. In this study, we first discovered that repeated and prolonged exposure to propofol-induced cognitive impairment in adult rodents. Then, we examined the property of hippocampal primary neurons and slices after propofol treatment in mice, including synaptic protein profile, dendritic spine density, as well as synaptic transmission. We found the distinctive change of the F-box only protein 22 (FBXO22), an F-box E3 ligase, during this process and further explored its role. Knockdown experiments showed the downregulation of FBXO22 restored the changes by propofol treatment on hippocampal primary neurons and attenuated propofol-induced hippocampal dependent cognitive dysfunction. Our results showed that FBXO22 is involved in the regulation of repeated propofol treatment induced changes of synaptic plasticity and cognitive dysfunction in adult mice. Repeated propofol treatment leads to cognitive dysfunction by regulating FBXO22 in adult rodents.